(untitled) (Research, Society and Development, 2020)
The banana (Musa ssp.) Is one of the most consumed fruits in the world, source of vitamins and minerals, acts in the fight against depression, anxiety, improves mood, and has good acceptance due to its sensory aspects and nutritional value. Given this, the present work aimed to elaborate and evaluate the sensorial aspects of the banana cake (Musa ssp.) With functional potential. This is an experimental, transversal and quantitative study, in which the product was prepared in the laboratories of Dietetic Technique and Sensory Analysis of Food belonging to the University Center of Science and Technology of Maranhão - UNIFACEMA, located in Caxias - MA. Three formulations were prepared and added to the oven at 250 ° C for 30 minutes. After preparation, microbiological analyzes were carried out at the Center for Studies on Food Research and Procedures - NUEPA at the Federal University of Piauí - UFPI. The sample consisted of 64 evaluators, for the sensory analysis, the nine-point Hedonic Scale was used and for the purchase intention, the five-point Hedonic Scale was used. The banana-based cake was well accepted by the evaluators, considering that all samples obtained a score higher than 7, considering the appearance, aroma, texture, flavor and global acceptance, in addition, no statistically significant difference was observed between the samples. As for the purchase intention, 74.48% of the evaluators stated that they would buy, and the microbiological analysis showed that the product was safe. In view of this, the prepared product was accepted by the evaluators and safe in relation to microbiological standards, therefore, it is a food option in the consumer market with healthy potential.